Developing and Integrating Digital Sources in an Accessible and Sustainable Online Platform for Adolescents and Young Adult Cancer Survivors: Collaborative Design Approach - Vlooswijk, Carla; Sleeman, Sophia HE; Pluis, Jonas; Bakker, Daphne; de Groot, Lisanne; Manten, Eveliene; Heine, Peter; Husson, Olga; van Eenbergen, Mies C; Vandekerckhove, Pieter (JMIR formative research, 2025)
Digital support for adolescent and young adult cancer survivors is fragmented and results in lacking a reliable overview of support services available to them. Collaborative design promises to integrate perspectives of diverse stakeholders and could help to develop an online platform, which increases access and has a long-term perspective. However, it has not yet been explored how collaborative design can be used more strategically to develop an online platform with these aims. This study aimed to explore how a collaborative design approach could be applied to develop an online platform for adolescent and young adult cancer survivors, focusing on three key objectives: integrating existing resources, improving accessibility, and ensuring long-term financial sustainability. In this action research study, we reflect on a collaborative design process to develop an online platform for adolescent and young adult cancer survivors. A quantitative questionnaire was sent out to adolescent and young adult cancer survivors and health care professionals. Stakeholders were actively engaged in stakeholder consensus meetings, and project management was carried out through monthly design meetings to facilitate coordination and decision-making of the development of the platform. Afterwards, a focus group was conducted among the project group to evaluate the collaborative design approach, analyzed using an inductive thematic approach. Through the collaborative design approach, several Dutch organizations collaborated to develop, enhance, and combine online services for adolescent and young adult cancer survivors and their relatives. A dedicated online "young and cancer" platform for adolescent and young adult cancer survivors was developed, which integrates different types of information tools and supportive interactive elements from different sources. The integration of different resources into one platform improves the access and user experience of adolescent and young adult cancer survivors when it comes to online support. Through the reflection about the collaborative process, three themes were identified: (1) value of stakeholder participation; (2) conditions for working with adolescents and young adults with lived experience; and (3) collaboration between adolescents and young adults with lived experience and professionals from different backgrounds and organizations. A collaborative design approach can be used to efficiently develop an online platform for adolescent and young adult cancer survivors. The collaboration among professionals, including online developers, researchers, and adolescents and young adults with lived experience facilitated a direct translation of insights into the platform, while the support of the national cancer platform provides long-term sustainability. This study highlights the importance of strategic stakeholder selection and the intense involvement of stakeholders through a collaborative design approach.